2022
DOI: 10.1080/17565529.2022.2028596
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the concepts of global climate change, adaptation, and human mobility: a political-ecological exploration in Vietnam’s Mekong Delta

Abstract: The complex relationship between human mobility and global climate change remains contested. In this viewpoint, the themes of human mobility, adaptation and climate change are explored from a political ecology perspective. A framework of political ecology of human mobility in relation to climate change is applied to the context of Vietnam's Mekong Delta (MKD). The Vietnamese government, popular media and academic studies often present the MKD in dystopian ways in which there is sometimes no more place for poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Some suggested approaches in the document advocate for a return to flood‐regime production, which is less focused on intensive rice and more on integrated aquaculture‐agriculture schemes (Tran et al, 2021). However, farmers who were pushed to intensify rice production in the past are now being asked by Resolution 120 to voluntarily shift to other systems, bear the financial and social risks of these changes and become high skill agricultural workers for high‐value crops (Bayrak et al, 2022). Such approaches to development ignore the deep roots of climate precarity that have been outlined here and which prove a disincentive for households in bearing the burdens of adaptation.…”
Section: Comparing Agrarian Change and Climate Precarity For Smallhol...mentioning
confidence: 99%
“…Some suggested approaches in the document advocate for a return to flood‐regime production, which is less focused on intensive rice and more on integrated aquaculture‐agriculture schemes (Tran et al, 2021). However, farmers who were pushed to intensify rice production in the past are now being asked by Resolution 120 to voluntarily shift to other systems, bear the financial and social risks of these changes and become high skill agricultural workers for high‐value crops (Bayrak et al, 2022). Such approaches to development ignore the deep roots of climate precarity that have been outlined here and which prove a disincentive for households in bearing the burdens of adaptation.…”
Section: Comparing Agrarian Change and Climate Precarity For Smallhol...mentioning
confidence: 99%
“…The study of [25] has demonstrated that the direction of suspended sediment movement depends on the prevailing monsoon direction. The coastal estuarine area in the Mekong Delta has undergone complex changes in its hydraulic regime due to climate change and upstream development [26]. The coast of Soc Trang has been extensively studied regarding the contribution of natural hydrodynamic sediment redistribution and erosion caused by human activities [25,[27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…This is the opposite for the coastal estuaries of the West Sea (Schmitt et al 2013). However, in the context of climate change and the development in the upstream, the hydraulic regime of the coastal estuarine area in the Mekong Delta has complicated changes, as a results, the amount of sediment also varies significantly (Bayrak et al 2022). In the coastal of Soc Trang, there are many studies on the contribution of natural hydrodynamic redistribution of sediments from man-induced erosion (Mai et al 2019;Marchesiello et al 2019;Nguyen et al 2022;Thanh et al 2019;Thanh et al 2017).…”
Section: Introductionmentioning
confidence: 99%